The invention of the passport: surveillance, citizenship and the state - Torpey, John C. (Cambridge studies in law and society, 2018)
This book presents the first detailed history of the modern passport and why it became so important for controlling movement in the modern world. It explores the history of passport laws, the parliamentary debates about those laws, and the social responses to their implementation. The author argues that modern nation-states and the international state system have 'monopolized the 'legitimate means of movement',' rendering persons dependent on states' authority to move about - especially, though not exclusively, across international boundaries. This new edition reviews other scholarship, much of which was stimulated by the first edition, addressing the place of identification documents in contemporary life. It also updates the story of passport regulations from the publication of the first edition, which appeared just before the terrorist attacks of 9/11, to the present day.